Prevalence of RhD variants among blood donors at Gulu Regional Blood Bank, Gulu, Northern Uganda - Ojok P; Oyet C; Webbo F; Mwambi B; Taremwa IM (Journal of Blood Medicine, 2017)
Polycarp Ojok,1,2 Caesar Oyet,1 Fred Webbo,1,3 Bashir Mwambi,1 Ivan M Taremwa1 1Institute of Allied Health Sciences, International Health Sciences University, Kampala, 2Gulu Regional Blood Bank, Gulu, 3Lancet Laboratories, Kampala, Uganda Aim/objective: The aim of this study was to determine the prevalence of RhD variant phenotypes among voluntary non-remunerated blood donors (VNRBDs) at Gulu Regional Blood Bank (GRBB), Northern Uganda. Materials and methods: We conducted a cross-sectional study, in which the first 4.0 mL of ethylenediaminetetraacetic acid (EDTA) blood samples were collected from VNRBDs and typed for their ABO and RhD blood group status using IgM and IgG monoclonal typing antisera, respectively. Blood samples that tested as RhD negative were further investigated for RhD variant phenotypes using indirect antihuman globulin hemagglutination technique. Results: We assayed 138 RhD-negative blood samples obtained from VNRBDs. Of these, 66.7% (n=92) were males. Their median age was 24.4 years (range, 14–33 years). Majority of the participants were of ABO blood group O (62.8%, n=86), followed by A (19.7%, n=27), then B (13.9%, n=19) and least AB (3.6%, n=6). The prevalence of RhD variant phenotypes was 0.7% (n=1; 95% confidence interval, 0.5–0.9). There was no statistical association of RhD variant phenotypes with donor gender, tribe and their ABO blood groups. Conclusion: This study has revealed a high prevalence of RhD variant among blood donors at GRBB in Northern Uganda. It further highlights a potential risk of alloimmunization, as the present blood typing practices do not identify RhD variant phenotypes. Keywords: Rh blood group, D variants, D antigen, weak D, partial D, Uganda